The Impact Of Dilan 1990 Movie On Students' Behavior At SMA Negeri 1 Of South Bengkulu - Gading Abiemayu Baskara; Sri Narti; Yanto Yanto (Penerbit Jurnal Indonesia, 2023)
This thesis is entitled The Impact of Dilan 1990 Movie on students’ behavior of at SMA Negeri 1 of South Bengkulu. This study aims to determine the impact of Dilan 1990 Movie on students’ behavior of at SMA Negeri 1 of South Bengkulu. This research uses quantitative research. The object of this research is the students of SMA Negeri 1 of South Bengkulu, the method used by the writer in this research is survey and documentation, the theory used in this research is the theory of Television Watching Pattern and theory Attribution. The data analysis technique used is the Likert Scale where the author uses the scale to determine the results of the answers from the respondents. The next stage in this test, the writer uses the correlation coefficient test to measure the strength of the correlation between the two variables based on the correlation coefficient interpretation, after that the correlation significance and determination coefficient test is carried out to see the effect of Dilan 1990 Movie on students’ behavior of at SMA Negeri 1 of South Bengkulu. In this study, the writer used the SPSS 26 application for the test. Based on the results of research and discussion on the Impact of Dilan 1990 Movie on students’ behavior of at SMA Negeri 1 of South Bengkulu, the correlation between the two variables is very low, insignificant and not unidirectional. This is shown from the results of the Correlation Coefficient test, the value obtained is -0,202 with a significance number of 0.05 (very low). Therefore, it can be concluded that there is no impact on students’ behavior of SMA Negeri 1 of South Bengkulu.